Literature Review: The Role of Ethics as Corporate Good Governance - Olii, Sinta; Lapuna, Dela Delvia A.; Mustapa, Anggi; Subula, Nafaldin; Badjeber, Fedyah (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
The economic progress of a country encourages the development of the business world. It encourages the emergence of new business actors, giving rise to quite sharp competition in the business world. This research aims to learn more about business ethics violations that often occur in the business environment. The method in this research is literature observation or literature study. The research results show that of the eight articles used in this literature observation, seven show a significant relationship between business ethics violations in companies.